Impact of physical facilities on discipline, extra-curricular activities and teaching and learning in Mable Secondary Schools, Uganda - Sulaiman, Afolasade A.; Shehu, Haliru; Hussaini, Nasiru (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study surveyed the impact of physical facilities on discipline, extra-curricular activities and teaching and learning in Mbale secondary schools, Uganda. A total of 369 respondents were randomly selected as sample for the study. Physical Facilities and School Activities Questionnaire (PFSAQ) was the instrument of data collection. PFSAQ reliability and validity values were 0.79 and 0.82 respectively. Results revealed that availability of physical facilities has huge impact on teaching and learning, co-curricular facilities and especially discipline. Based on the findings, it was recommended that government should employ trained counsellors as members of staff in schools to assist students in dealing with adjustment problems and keep improving on school facilities to ensure effective teaching and learning and active participation in co-curricular activities. Administrators and teachers are encouraged to motivate and facilitate students’ participation in co-curricular activities within schools and among students.